Effect of Complex Contrast Training on Change of Direction Performance in Team-Sport Athletes: A Meta-Analysis - Shengfa Lin; Zhijie Yan; Tengyu Xu; Huisong Xie; Ruidong Liu (Applied Sciences)
(1) Background: Change of direction (COD) is crucial for agility in team sports. Complex contrast training (CNT), alternating between heavy and light exercises, is a newer method currently gaining attention, but its effectiveness compared to others (strength training, ST; plyometric training, PT; complex descending training, DT; complex ascending training, AT) is unclear. (2) Methods: A systematic review and meta-analysis following PRISMA guidelines included studies with CNT interventions. The effect size (ES) was measured using Hedges’ g, with subgroup analyses for moderating factors. (3) Results: CNT improved COD performance more than PT (ES = 0.65), ST (ES = 0.88), and controls (ES = 1.24), with no significant difference from DT (ES = −0.08) or AT (ES = 0.19). CNT was particularly effective for athletes under 18 (ES = 1.13), females (ES = 1.59), amateurs (ES = 1.02), and COD measures with more than three turns (ES = 1.08). (4) Conclusions: CNT enhances COD performance, proving superior to standalone strength or plyometric training. However, its effectiveness is comparable to other combined-training models, suggesting that the integration of high-load strength and high-velocity power exercises is the primary driver of adaptation. The benefits are most pronounced in younger, female, and amateur athletes. Future large-scale studies are needed to confirm these findings and refine protocols for diverse populations.